Nahwu Concept According to Imam Sibawaih and Ibrahim Mustafa in Arabic Linguistics (Comparative Studies of Syntax) - Fatkhur Roji (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
The process of analyzing Arabic syntax has occurred from classical to modern, and in terms of understanding, there has been development and deepening of the discussion. So that the concept in the classical and modern periods is focused on the thoughts of Imam Sibawaih and Ibrahim Mustafa as a whole who have become representatives of both Arabs and non-Arabs. This research uses a Literature Review Design, library research or literature study (literature review, literature research), this research uses a comparative approach or comparison, it is educational research that uses the technique of comparing a object with other objects.This research uses a comparative approach. Both figures have their own methods, the methods used by classical figures to compose Nahwu using sama'i, qiyasi, ijma', ta'lil, istihsan and istishab with a philosophical and theological approach. Meanwhile, the method used by modern figures in compiling Nahwu uses tanziriyyah and tatbiqiyyah. The results of this research explain that the concept of nahwu according to Sibawaih in developing Nahwu lies in the classification of i'rab for nouns (ism) into rofa', nasb and khafd. Meanwhile, the concept put forward by Imam Sibawaih was simplified by Ibrahim Mustafa who said that i'rab consists of dammah and kasrah. Ibrahim Mustafa did not consider fathah an i'rab.This research only reveals the similarities and differences of nahwu, and only focuses on the two figures Imam Sibawaih and Ibrahim Mustafa, so that the results of these findings can be regenerated to be more complete and detailed. However, this research can be a reference for further research on these two figures. The researcher suggests that further research emphasize more on the implementation of Imam Sibawaih and Ibrahim Mustafa's nahwu using the Qualitative Field Method.